Strategi Pengelolaan Kekayaan (Aset) Daerah Dalam Meningkatkan Kinerja Pemda Kotawaringin Barat - Tiur Roida Simbolon; Alexandra Hukom; Feby Adila Indria Sutrisno; Ana Lesdiana; Novia Fransiska; Ella Priskila (FKIP, Universitas Palangka Raya, 2023)
The goal of this research was to investigate and assess regional asset management at the West Kotawaringin Regional Asset and Financial Management Agency (BPKAD). The purpose of this research is to better understand the significance of regional asset management in the context of regional financial management, as well as how regional asset management may help to promote local revenue (PAD) and development in the area. Furthermore, this study intends to examine the stages of regional asset management, from acquisition/receipt through disposal, as well as the performance of local governments in managing regional assets. This work was written utilizing a qualitative descriptive methodology, which is a sort of qualitative research.The goal of this research is to get a better knowledge of regional asset management and the significance of regional development. The findings of this study are also expected to provide recommendations and input to the West Kotawaringin Regional Asset and Financial Management Agency in order to improve the effectiveness and efficiency of regional asset management and support the achievement of regional development goals